(untitled) (International Journal of Current Engineering and Technology, 2014)
Handling generally refers to how a vehicle responds when it turn. Handling characteristics of the vehicles are closely related to driving safety. Handling characteristics of road vehicles refer to its response to steering commands and to environmental inputs, such as wind gust and road disturbances that affect its direction of motion. Many traffic accidents are caused by undesired and unexpected handling behavior of the vehicle. Hence it is necessary to understand the handling characteristics of the vehicle. The fundamental understeer/oversteer signature of a vehicle has evaluated through steady state circular skid pad testing according to one of the four methodologies outlined in the SAE J266 circle test. These tests evaluate a vehicle’s fundamental handling behavior, but are insufficient to fully establish its yaw stability and control characteristics and performance envelope. Transient testing of the vehicle is also necessary because vehicles are not operated under steady state conditions. This becomes of greatest importance in an emergency situation where a driver must respond quickly. For good handling and control, it is necessary for a vehicle to understeer in circular skid pad testing. Additionally, the vehicle must not become yaw unstable in a transient test (J-turn). In the present work, handling tests have been conducted on passenger vehicle Testing Laboratory.